An Unusual Psychiatric Emergency: Herpes Simplex Encephalitis - H. Doyle; J. Varian (Behavioural Neurology)
A case of fatal herpes simplex virus (HSV) encephalitis, presenting as a psychiatric emergency, is reported. The possibility of HSV encephalitis presenting mainly or solely with psychiatric symptoms is highlighted. HSV can cause a severe form of encephalitis which may present with mainly psychiatric symptoms in some cases. Early treatment with anti-viral agents can reduce mortality and morbidity, but accurate early diagnosis may be very difficult. HSV encephalopathy may mimic psychiatric illness and has been likened to syphilis as the great imitator. The case presented here should serve to raise awareness of the psychiatric features and the need to consider this diagnosis in patients with atypical behavioural disturbance.